Pengaruh Ekstrak Ikan Gabus Dengan Peningkatan Kadar Albumin Pada Pasien Sindrom Nefrotik - Syahrizal Syahrizal; Aliya Salsabila; Ardini Sabrina (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2023)
Nephrotic syndrome is a collection of symptoms characterized by massive proteinuria, hypoalbuminemia, edema and hypercholesterolemia. Snakehead fish contains important nutrients such as protein, omega-3 fatty acids, vitamins and minerals. Protein is the main building material in the body and is needed for albumin synthesis. Adequate protein consumption can provide the essential amino acids needed for albumin production in the body, thereby increasing albumin levels in the blood. The purpose of this study was to explain that snakehead fish extract has an effect on increasing albumin levels in patients with nephrotic syndrome based on a literature review. The research method uses a literature review study. The results of the study based on some of the literature that has been reviewed found that snakehead fish extract has an effect on increasing albumin levels in patients with nephrotic syndrome.